KUALITAS DAN TINGKAT PENCEMARAN AIR WADUK TITAB, BULELENG - Ayu Meiliana Laksmi Dewi; Ni Ketut Ayu Juliasih; I Nyoman Arsana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2022)
Monitoring water sources is essential to ensure the quality and quantity, one of which is in the Titab Reservoir. The purpose of the study was to assess the water quality and amount of pollution in the Titab reservoir in terms of physical, chemical, and microbiological characteristics, as well as the NVC of Tawes (Barbonymus gonionotus) fish. There are five station points for water sampling and 10 test parameters related to water quality. Data analysis compares test results with second-class water quality standards (Bali Governor Regulation No. 16/2016), IP value (pollution index), and NVC with Furton's equation. The test results obtained that the water in the Titab reservoir has a temperature of 28.97oC, TSS (0.18 mg/L), pH (8.82), BOD (3.22 mg/L), COD (16.70 mg/L), DO (6.77 mg/L), Total Phosphate (0.12 mg/L), Nitrate (0.19 mg/L) and Fecal Coliform (960 MPN/100 mL), the IP value was 1.39, and the NVC was 1.65. Thus, the pH, BOD, and Fecal Coliform levels of the Titab reservoir water did not match the specified limits, although the other parameters satisfied the water quality norms. The Titab reservoir's water is classed as mildly contaminated with the NVC value of tawes fish, referring to the Titab reservoir's polluted water. Keywords: Tawes Fish, Titab Reservoir, Water pollution, Water quality.